TRPM2 Is Not Required for T-Cell Activation and Differentiation - Lory, Niels C.; Nawrocki, Mikolaj; Corazza, Martina; Schmid, Joanna; Schumacher, Valéa; Bedke, Tanja; Menzel, Stephan; Koch-Nolte, Friedrich; Guse, Andreas H.; Huber, Samuel; Mittrücker, Hans-Willi (Frontiers in Immunology, 2022)
Antigen recognition by the T-cell receptor induces a cytosolic Ca2+ signal that is crucial for T-cell function. The Ca2+ channel TRPM2 (transient receptor potential cation channel, subfamily M, member 2) has been shown to facilitate influx of extracellular Ca2+ through the plasma membrane of T cells. Therefore, it was suggested that TRPM2 is involved in T-cell activation and differentiation. However, these results are largely derived from in vitro studies using T-cell lines and non-physiologic means of TRPM2 activation. Thus, the relevance of TRPM2-mediated Ca2+ signaling in T cells remains unclear. Here, we use TRPM2-deficient mice to investigate the function of TRPM2 in T-cell activation and differentiation. In response to TCR stimulation in vitro, Trpm2-/- and WT CD4+ and CD8+ T cells similarly upregulate the early activation markers NUR77, IRF4 and CD69. We also observe regular proliferation of Trpm2-/- CD8+ T cells and unimpaired differentiation of CD4+ T cells into Th1, Th17 and Treg cells under specific polarizing conditions. In vivo, Trpm2-/- and WT CD8+ T cells show equal specific responses to Listeria monocytogenes after infection of WT and Trpm2-/- mice and after transfer of WT and Trpm2-/- CD8+ T cells into infected recipients. CD4+ T-cell responses were investigated in the model of anti-CD3 mAb induced intestinal inflammation, which allows analysis of Th1, Th17, Treg and Tr1-cell differentiation. Here again, we detected similar responses of WT and Trpm2-/- CD4+ T cells. In conclusion, our results argue against a major function of TRPM2 in T-cell activation and differentiation.